The Effect of Multiple-Slot Substitution Drill in Teaching Present Continuous Tense to Improve Students’ Speaking Achievement at the Eighth Grade of SMP IT Asy-Syadzili Pakis-Malang - Muhammad Yasminto; Susanto, M. Agus (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
This study investigated students’ speaking achievement on present continuous tense using multiple-slot substitution drill at the eighth grade students of SMP IT Asy-Syadzili Pakis-Malang. Designed used in this study was true experimental research conducted with one experimental group taught present continuous tense using multiple-slot substitution drill and control group without multiple-slot substitution drill. To collect the data, the researcher used speaking post-test in oral test form. In analyzing the data, the researcher used IBM spss statistic versions. 20 application of independent sample t.test to know the differences between experimental and control groups. After applying the statistical computation, it was found that the mean score of experimental group (X) in post-test 53.58 with standard deviation 3.951 was higher than the mean score of control group (Y) in post-test 41.57 with standard deviation 2.750 . So it can be concluded that students taught present continuous tense using multiple-slot substitution drill achieve better than taught without multiple-slot substitution drill at the eighth grade students of SMP IT Asy-Syadzili Pakis-Malang